Acetylene-free synthesis of vinyloxy pyridine and quinoline. Issue 51 (21st December 2016) - Hamdi, Abdelrahman; Mostafa, Amany S.; Watat, Cedric Nana; Laurent, Mathieu Y.; Ben Ayed, Kawther; Selim, Khalid B.; Dujardin, Gilles
Graphical abstract: Highlights: State of art reviewed on vinylation methods of hydroxy pyridines/quinolines. 2- & 4-hydroxy pyridines/quinolines: N- vinylation with known copper-based methods. First synthesis of 4-vinyloxy pyridine & 4-vinyloxy quinoline from bromides. Abstract: Copper-catalyzed vinylation of 2- and 4-hydroxy pyridine and quinoline affords exclusively N- vinylation products. However, vinyl ethers of 4-hydroxy pyridine and quinoline can be prepared via a three-step sequence involving copper-catalyzed C-O cross coupling reaction of the corresponding N- heteroaryl bromides with ethylene glycol, chlorination of the terminal alcohol, and dehydrohalogenation of the β-chloro ethers. Although not efficient in 2-hydroxy series, this method can be conveniently applied to the preparation of various aza-aryl vinyl ethers in moderate to good overall yields.